Water temperature affects the biotransformation and accumulation of a psychoactive pharmaceutical and its metabolite in aquatic organisms - Cerveny, D; Fick, J; Klaminder, J; McCallum, E S; Bertram, M G; Castillo, N A; Brodin, T (Environment international, 2021)
Pharmaceutically active compounds (PhACs) have been shown to accumulate in aquatic and riparian food-webs. Yet, our understanding of how temperature, a key environmental factor in nature, affects uptake, biotransformation, and the subsequent accumulation of PhACs in aquatic organisms is limited. In this study, we tested to what extent bioconcentration of an anxiolytic drugs (temazepam and oxazepam) is affected by two temperature regimes (10 and 20 °C) and how the temperature affects the temazepam biotransformation and subsequent accumulation of its metabolite (oxazepam) in aquatic organisms. We used European perch (Perca fluviatilis) and dragonfly larvae (Sympetrum sp.), which represent predator and prey species of high ecological relevance in food chains of boreal and temperate aquatic ecosystems. Experimental organisms were exposed to target pharmaceuticals at a range of concentrations (0.2-6 µg L-1) to study concentration dependent differences in bioconcentration and biotransformation. We found that the bioconcentration of temazepam in perch was significantly reduced at higher temperatures. Also, temperature had a strong effect on temazepam biotransformation in the fish, with the production and subsequent accumulation of its metabolite (oxazepam) being two-fold higher at 20 °C compared to 10 °C. In contrast, we found no temperature dependency for temazepam bioconcentration in dragonfly larvae and no detectable biotransformation of the parent compound that would result in measurable concentrations of oxazepam in this organism. Our results highlight that while organisms may share the same aquatic ecosystem, their exposure to PhACs may change differently across temperature gradients in the environment.
Keywords: Biotransformation; léčivé přípravky; Temperature; Drug; Pharmaceutical Preparations; Ecosystem; teplota; zvířata; Fish; Benzodiazepine; Aquatic Organisms; Aquatic invertebrate; vážky; Odonata; okounovití; voda; Temazepam; Perches; Water Pollutants, Chemical; Dragonfly; biotransformace; Water; Animals; vodní organismy; chemické látky znečišťující vodu; ekosystém